Image and graphics : 9th International Conference, ICIG 2017, Shanghai, China, September 13-15, 2017, revised selected papers /: 9th International Conference, ICIG 2017, Shanghai, China, September 13-15, 2017, revised selected papers. ([2017]) - Unknown
No abstract available